On Schur–Nevanlinna–Pick Indefinite Interpolation Problem - Derkach, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
The Schur–Nevanlinna–Pick interpolation problem is considered in the class of generalized Schur functions and reduced to the problem of the extension of a certain isometric operator V that acts in the Pontryagin space. The description of the solutions of this problem is based on the theory of the resolvent matrix developed by Krein.